Host-Pathogen Interaction as a Novel Target for Host-Directed Therapies in Tuberculosis - Abreu, Rodrigo; Giri, Pramod; Quinn, Fred (Frontiers in Immunology, 2020)
Tuberculosis (TB) has been a transmittable human disease for many thousands of years, and M. tuberculosis is again the number one cause of death worldwide due to a single infectious agent. The intense 6- to 10-month process of multi-drug treatment, combined with the adverse side effects that can run the spectrum from gastrointestinal disturbances to liver toxicity or peripheral neuropathy are major obstacles to patient compliance and therapy completion. The consequent increase in multidrug resistant TB (MDR-TB) and extensively drug resistant TB (XDR-TB) cases requires that we increase our arsenal of effective drugs, particularly novel therapeutic approaches. Over the millennia, host and pathogen have evolved mechanisms and relationships that greatly influence the outcome of infection. Understanding these evolutionary interactions and their impact on bacterial clearance or host pathology will lead the way toward rational development of new therapeutics that favor enhancing a host protective response. These host-directed therapies have recently demonstrated promising results against M. tuberculosis, adding to the effectiveness of currently available anti-mycobacterial drugs that directly kill the organism or slow mycobacterial replication. Here we review the host-pathogen interactions during M. tuberculosis infection, describe how M. tuberculosis bacilli modulate and evade the host immune system, and discuss the currently available host-directed therapies that target these bacterial factors. Rather than provide an exhaustive description of M. tuberculosis virulence factors, which falls outside the scope of this review, we will instead focus on the host-pathogen interactions that lead to increased bacterial growth or host immune evasion, and that can be modulated by existing host-directed therapies.